Thermogravimetric analysis of chemical reduction processes to produce oxygen from lunar regolith. (February 2020) - Reiss, P.; Kerscher, F.; Grill, L.
Abstract: Various processes exist for extracting oxygen from lunar regolith via chemical reduction for In-Situ Resource Utilization (ISRU). Reduction with hydrogen, methane, possibly carbon monoxide, or gas mixtures are the processes that have predominantly been studied and discussed for this purpose over the past decades. However, it remains unclear how applicable these processes are to lunar highland regolith and how well they compare at temperatures below 1000 °C, above which the material starts sintering and melting. To approach this knowledge gap, a direct comparison of the reduction of pure ilmenite and the highland type lunar regolith simulant NU-LHT-2M was performed by means of thermogravimetric analysis (TGA). Pure nitrogen, hydrogen, and methane were used as process gases for the TGA. The results show that ilmenite is a good reference material for the reduction with hydrogen, which starts at temperatures around 500 °C. Hydrogen can also be used to reduce the very low ilmenite content in NU-LHT-2M, but due to the low weight loss and additional thermal decomposition of several impurities in the simulant this reduction is hardly visible in the TGA. The reduction of ilmenite via methane was demonstrated to be possible in the investigated temperature range. However, the deposition of carbon on the sample lead to a strong contamination of the measurement setup and a steep weight increase that overcompensated the weight loss expected from the release of oxygen. For NU-LHT-2M the reduction via methane is more difficult to assess because of the low weight change and the less pronounced weight loss. Several potential side reactions with decomposition products, such as water, carbon dioxide, and carbon monoxide, at higher temperature additionally complicate the interpretation of results. Highlights: Ilmenite and NU-LHT-2M were reduced with both hydrogen and methane below 1000 °C. Weight losses were measured via TGA under flowing nitrogen, hydrogen, and methane. Methane decomposition enables the reduction of ilmenite via hydrogen and carbon. Carbon deposition occurs above 900 °C and leads to significant contamination. NU-LHT-2M noticeably changes its appearance after thermal treatment with hydrogen.